Effectiveness of Herbal and Non-Herbal Toothpastes in Reducing Dental Plaque Accumulation - Citra L. Yuwono; Benny M. Soegiharto; Fadli Jazaldi (Faculty of Dentistry, Universitas Indonesia, 2013)
Maintaining good oral hygiene in orthodontic patients is important and as the community interest in herbal ingredients increases, herbal toothpaste was developed. Its effectiveness against dental plaque accumulation is still under debate. Herbal toothpaste has not been tested in fixed orthodontic patients. Objective: To study the effectivenes differences between herbal toothpaste and non-herbal toothpaste. Methods: This randomized, double blind clinical trial was participated by 16 subjects aged range 15-35 years who were planned for fixed orthodontic. The subjects were divided into two groups based on the type of toothpaste used. Plaque accumulations were measured according to Löe and Sillness plaque index on Ramfjord teeth before and two weeks after bonding. Results: Wilcoxon test result showed there was no significant reduction of plaque index on herbal toothpaste usage nor significant increase on non-herbal toothpaste usage. Mann-Whitney test showed no significant differences between herbal and non-herbal toothpaste. Conclusion: There was no significant differences in plaque acummulation between usage of herbal toothpaste nor usage of non-herbal toothpaste. There was no significant effectiveness differences between those toothpastes in fixed orthodontic patients, although herbal toothpaste usage showed a reduction of plaque index, whereas non-herbal toothpaste usage showed an increase of plaque index. DOI: 10.14693/jdi.v19i3.143